SIMULATIONS OF FLUID INTERFACES USING CONSERVATIVE FRONTTRACKING METHOD FOR 2D EULER SYSTEM - M.A, Ullah; M.U, Khandaker; D., Mao, (Malaysian Journal of Science, 2016)
In this paper, we use a conservative front-tracking method for 2D Euler system to do interface simulation. In this method, the movement of fluid interfaces is locally described by 1D Partial Differential Equation (PDE's) derived from the Euler system, and tracking is realized by numerically solving these 1D PDE's in a conservative fashion. We use this method to simulate the Richtmyer-Meshkov instability. Our numerical results are compared with the nonlinear theory developed by Zhang and Sohn (1997) and seem to agree both qualitatively and quantitatively. Keyword: Nonlinear growth rate, Conservative front-tracking, Richtmyer-Meshkov instability